2017
DOI: 10.1016/j.celrep.2017.05.028
|View full text |Cite
|
Sign up to set email alerts
|

Oxysterol-Binding Protein-Related Protein 1L Regulates Cholesterol Egress from the Endo-Lysosomal System

Abstract: Lipoprotein cholesterol is delivered to the limiting membrane of late endosomes/lysosomes (LELs) by Niemann-Pick C1 (NPC1). However, the mechanism of cholesterol transport from LELs to the endoplasmic reticulum (ER) is poorly characterized. We report that oxysterol-binding protein-related protein 1L (ORP1L) is necessary for this stage of cholesterol export. CRISPR-mediated knockout of ORP1L in HeLa and HEK293 cells reduced esterification of cholesterol to the level in NPC1 knockout cells, and it increased the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
133
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(137 citation statements)
references
References 39 publications
3
133
1
Order By: Relevance
“…Compared to the short (2 h) OSW-1 treatment, the long (72 h) exposure of cells to siRNA against OSBP is more likely to favor compensatory effects preventing toxic cholesterol accumulation at the ER. In this respect, we noted that cholesterol transfer proteins acting between the ER and late endosomal compartments have been very recently identified (Wilhelm et al, 2017;Zhao & Ridgway, 2017).…”
Section: Inhibition Of Endogenous Osbp Affects Intracellular Sterol Dmentioning
confidence: 96%
“…Compared to the short (2 h) OSW-1 treatment, the long (72 h) exposure of cells to siRNA against OSBP is more likely to favor compensatory effects preventing toxic cholesterol accumulation at the ER. In this respect, we noted that cholesterol transfer proteins acting between the ER and late endosomal compartments have been very recently identified (Wilhelm et al, 2017;Zhao & Ridgway, 2017).…”
Section: Inhibition Of Endogenous Osbp Affects Intracellular Sterol Dmentioning
confidence: 96%
“…As a result of this newly formed membrane contact sites, the lysosome is tethered to the ER and the dynein‐dynactin motor is displaced from RILP. Within the ER contact sites formed by ORP1L/VAP interaction between the two compartments, cholesterol is transferred from lysosomes to the ER . Overall, ORP1L‐regulated endosomal motility is responsible for interacting with the ER protein VAP that then determines clustering of lysosomes in cholesterol‐rich conditions and their immobilization in a scattered state when cholesterol is depleted.…”
Section: Lysosomal Positioning Regulated By Other Organellesmentioning
confidence: 99%
“…Cholesterol accumulation in lysosomes of cells lacking ORP5, suggests that ORP5 may be an acceptor for cholesterol mobilized by the NPC2-NPC1 system (Du et al, 2011). The OSBP-related protein 1L (ORP1L), which was previously implicated in lysosomal positioning in response to cholesterol levels (Rocha et al, 2009), was recently found to mediate transport of cholesterol from LE/LY to the ER in a VAPA/B dependent manner (Zhao and Ridgway, 2017). Cells lacking ORP1L showed significant accumulation of cholesterol at the lysosomal limiting membrane, with concomitant reduction of cholesterol esterification in the ER, suggesting blockage of an important route for cholesterol delivery to the ER.…”
Section: Mechanisms Of Lipid Export From the Lysosome (Le/ly)mentioning
confidence: 99%